Calcium Mine Exploration in Lebak: A Tafsír ‘Ilmi Perspective on Natural Resource Management - Syahid, M Raihan; El-Habsa, Isna Tsania; Shidqi, Muhammad Nikola; Rosa, Andi; Sutiani, Nina (AN NUR: Jurnal Studi Islam, 2025)
This research aims to examine the practice of artisanal mining of Kalimaya stone in Lebak Regency through the tafsir ‘ilmi approach, which is a method of interpreting the Qur'an that integrates the text of revelation with contemporary scientific reality. This topic is essential considering that artisanal mining often takes place without an ethical or sustainability framework, and lacks a touch of religious values, even though the majority of Indonesian people are Muslim. The research uses an explorative qualitative method with an interdisciplinary approach, which combines thematic analysis of kauniyy?t verses, geological data on Kalimaya stone, and in-depth interviews with miners and local community leaders. The results show that tafsir ‘ilmi can form an Islamic-based ecological ethics framework that is applicable in mining practices. Through the reconciliation between the principles of tawhid, khilafah, amanah, and 'ad?lah, this research creates an Islamic Geoethics framework as an alternative ethical paradigm in mineral resource management. These findings not only enrich contemporary interpretive discourse but also offer practical contributions in the form of mining governance based on spiritual, social, and ecological sustainability values.